VISUAL MEDIA UTILIZATION IN MASTERING ENGLISH VOCABULARY OF HEARING-IMPAIRED STUDENTS - Agus Husein As Sabiq; Maulani Anjani Sukirno (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
Hearing-impaired students are visual learners. That’s why the visual media selection will be the most appropriate media assistance for teachers, especially in teaching vocabulary. This research aimed to investigate the use of visual media and teacher challenges in developing English vocabulary for hearing-impaired students. This research used a qualitative descriptive approach. The participants of the research were an English teacher and eight hearing-impaired students in the 8th grade of SMPLB N Banjarnegara. The data were obtained through observation, interviews, and students’ self-reports. The researchers found that the teacher used limited visual media at around the combination of a whiteboard, images, picture dictionary, and realia. The teacher used a whiteboard to write and draw the material. Images and picture dictionary were used to give an overview and insight to the students and sign language was used as language instruction in the teaching process. Less practice pronouncing the words and misunderstanding on reading the lips movements became the challenges for the teacher. Furthermore, the teacher has less technical skills to utilize technological-based media in delivering the materials.